ANALISIS FAKTOR PENYEBAB TERHADAP SALAH SATU PIHAK YANG MELAKUKAN KASUS INGKAR JANJI MENIKAH (STUDI KASUS PADA RUMAH PEREMPUAN KUPANG) - Simon, Mario Stanic; Usman, Siti Ramlah; Dinata, Husni Kusuma (Petitum Law Journal, 2023)
Marriage is the behavior of creatures created by God Almighty so that life in the natural world can reproduce. Regarding marriage, it is regulated in Articles 26 to 102 of the Civil Code, where the general provisions in the Civil Code are contained in Article 26 of the Civil Code which reads: "The law views marriage only in terms of civil relations." Starting from these provisions, the Civil Code does not consider the importance of religious elements. The research results show: The factors that cause broken promises to marry are because the family does not support or disapprove of their relationship, the perpetrator is just having fun (not seriously dating), and the perpetrator is afraid of starting a family so they choose to run away or are irresponsible , so that the NGO provides this solution. So far, cases of broken promises to marry have been difficult to bring to legal proceedings because there is no legal payment, so the resolution of cases of broken promises to marry is mostly resolved within the family, in this case the victim asks for compensation in the form of a customary fine. The author's conclusions are: The factors that cause one party to break their promise to marry are that the perpetrator is not ready to get married and the relationship between the perpetrator and the victim is not approved by both parents because the perpetrator and victim are still students. The legal consequences for the party who breaks their promise to marry is that the victim's family asks for responsibility in the form of fines, some in the form of money and animals, because so far cases of broken promises to marry handled by the NGO Kupang Women's House are difficult to bring to legal proceedings because there is no legal payout.